PANDANGAN MASYARAKAT TERHADAP WANITA SEBAGAI PENDENDANG DALAM ACARA BAGURAU LAPIAK DI PAYAKUMBUH - Syafniati, Syafniati (Humanus, 2014)
Bagurau Lapiak is one of the types of saluang dendang (sing along with saluang—a type of recorder—play) performance conducted in the corridors of Payakumbuh stores, using lapiak (mat) for seat. Bagurau Lapiak is organized by a group ‘pagurauan’ (jokers) held on evenings starting at 21.00 until dawn. The singer (‘pendendang’) in the show is a woman who will fulfill the request of the audience to sing and play certain tunes by giving some amount of money to a committee called janang. Previously all singers in Minangkabau are men; women singers are considered to violate traitional and religious norms and it is not appropriate for women to sing along with the men in public let alone at night. However, in the case of saluang pendendang, women sungers play an important role in attracting the ‘joke addict’ in saluang bagurau (joking) activity. This paper aims to reveal the form of presentation of bagurau lapiak in Payakumbuh and the society's view of women as singer. This stuy used qualitative descriptive analysis method with cultural anthropology approach to music which can be seen through the behavior of musical physic and verbal as cultural facts of individuals and community groups. The music and the communities’ behavior have a very close relation. This study also uses feminimisme theory to explain women’s role in the saluang dendang show. The result shows that the tunes, the rhymed text that are sung by women are a kind of communication between the singers and the audience. In the other hand, people support as well as criticize the woman singer based on traditional, religious, and performing art values. Keywords: pendendang women, Bagurau Lapiak, community views